Del Nido Cardioplegia for Myocardial Protection in Adult Cardiac Surgery: A Systematic Review and Meta-Analysis. Issue 3 (May 2018) - Li, Yongnan; Lin, Hao; Zhao, Yinglu; Li, Zhenzhen; Liu, Debin; Wu, Xiangyang; Ji, Bingyang; Gao, Bingren
Abstract : Cardioplegia is an important strategy for myocardial protection during cardiac surgery. This meta-analysis was to compare the effects of del Nido and conventional cardioplegia in adult patients. Systematic searches were performed to identify studies using PubMed, Embase, the Cochrane Library, and the International Clinical Trials Registry Platform. A total of nine studies were included. Cardiopulmonary bypass and cross-clamp time were significantly shorter in the del Nido than conventional cardioplegia (mean difference [MD]: −7.52, 95% confidence interval [95% CI]: −14.76 to −0.29, p = 0.04; MD: −5.74, 95% CI: −10.14 to −1.34, p = 0.01). During the operation, cardioplegia volume and blood glucose level were lower in the del Nido group (MD: −522.53, 95% CI: −926.68 to −118.37, p = 0.01; standardized mean difference [SMD]: −1.11, 95% CI: −1.74 to −0.48, p = 0.0006). Ventilation time and length of intensive care unit were decreased significantly with del Nido cardioplegia (MD: −1.05, 95% CI: −1.79 to −0.31, p = 0.006; MD: −0.65, 95% CI: −0.92 to −0.38, p < 0.00001). There were no differences in myocardial enzyme, postoperative inotropic support, atrial fibrillation, hospital, and mortality between the two groups. In adult cardiac surgery, myocardial protection used with the del Nido or conventional cardioplegia solution yield similar short-term clinical outcomes.